Tanzania's first Marburg Viral Disease outbreak response: Describing the roles of FELTP graduates and residents. - Ally Kassim Hussein; Rogath Saika Kishimba; Azma Ayoub Simba; Loveness John Urio; Nsiande Andrew Lema; Vida Makundi Mmbaga; Beatrice Kemilembe Mutayoba; Nelson Edwin Malugu; Devotha Leonard; Joseph Hokororo; Maria Ezekiely Kelly; Albert Paschal; et al. (PLOS Global Public Health)
Viral Haemorrhagic Fever Outbreak presents a significant public health threat, requiring a timely, robust, and well-coordinated response. This paper aims to describe the roles of the Tanzania Field Epidemiology and Laboratory Training Program (TFELTP) graduates and residents in responding to Tanzania's first Marburg Viral Disease (MVD) outbreak. We performed a secondary data analysis using a range of documents, such as rosters of deployed responders and the TFELTP graduate and resident database, to count and describe them. Additionally, we conducted an exploratory textual analysis of field deployment reports and outbreak situational reports to delineate the roles played by the residents and graduates within each response pillar. A total of 70 TFELTP graduates and residents from different regions were involved in supporting the response efforts. TFELTP graduates and residents actively participated in several interventions, including contact tracing and follow up, sensitising clinicians on surveillance tools such as standard case definitions, alert management, supporting the National and Kagera Regional Public Health Emergency Operations Centres, active case search, risk communication, and community engagement, coordination of logistics, passenger screening at points of entry, and conducting Infection Prevention and Control (IPC) assessments and orientations in 144 Health Facilities. The successes achieved and lessons learned from the MVD response lay a foundation for sustained investment in skilled workforce development. FELTP Training is a key strategy for enhancing global health security and strengthening outbreak response capabilities in Tanzania and beyond.